Model Matematika Sistem Persediaan (Q, R) Yang Terkait Dengan Mutu Barang Dan Informasi Permintaan Lengkap - Agus Sukmana (Department of Mathematics, Hasanuddin University, 2007)
This paper deals with an inventory model for continuous review (Q, r) where there are some proportions of defective items in the ordered items. The number of defective items in a lot vary and it is assumed that their proportions follow a beta distribution. Lead time demand is a random variable, its distribution and parameters are known. This model also accommodates a condition where lost sales and back order policy are implemented in one cycle with different proportions of defective items. Numerical example is also given for illustration.